Use of Amniotic Membrane and Its Derived Products for Bone Regeneration: A Systematic Review - Etchebarne, Marion; Fricain, Jean-Christophe; Kerdjoudj, Halima; Di Pietro, Roberta; Wolbank, Susanne; Gindraux, Florelle; Fenelon, Mathilde (Frontiers in Bioengineering and Biotechnology, 2021)
Thanks to their biological properties, amniotic membrane (AM) and its derivatives are considered as an attractive reservoir of stem cells and biological scaffolds for bone regenerative medicine. The objective of this systematic review was to assess the benefit of using AM and amniotic membrane-derived products for bone regeneration. An electronic search of the MEDLINE – Pubmed database and the Scopus database was carried out and the selection of articles was performed following PRISMA guidelines. This systematic review included 42 articles taking into consideration the studies in which AM, amniotic-derived epithelial cells (AECs) and amniotic mesenchymal stromal cells (AMSCs) show promising results for bone regeneration in animal models. Moreover, this review also presents some commercialized products derived from AM and discusses their application modalities. Finally, AM therapeutic benefit is highlighted in the reported clinical studies. This study is the first one to systematically review the therapeutic benefits of AM and amniotic membrane-derived products for bone defect healing. The AM is a promising alternative to the commercially available membranes used for guided bone regeneration. Additionally, AECs and AMSCs associated with an appropriate scaffold may also be ideal candidates for tissue engineering strategies applied to bone healing. Here, we summarized these findings and highlighted the relevance of these different products for bone regeneration.